DAMPAK MINUMAN KERAS SOPI TERHADAP PERILAKU REMAJA DITINJAU DARI PERSPEKTIF KESEJAHTERAAN SOSIAL - Josephus Noya (BADATI, 2022)
Along with the development of the era, the abuse of liquor or alcohol is a fairly growing problem in the world and also results in the death rate of people aged 15-20 years. Prolonged alcohol use can cause various health-related problems, for example diseases caused by excessive consumers are brain tissue damage, liver disease, digestive system disorders, gland disorders, muscle system disorders, heart damage and cancer. According to Dafidov (1981) said that the habit of consuming alcohol can interfere with health, especially if consumed in excess and continuously can lead to disturbances in liver function and damage to the heart. Sopi is a type of traditional drink from Maluku with a fairly high level of consumption in the community. Sopi drinks are like illegal drugs that are specifically consumed at certain times, such as the ongoing activities of traditional events in the community. The availability of sopi in traditional events is a tradition from the ancestors in ancient times until now. Traditional sopi drinks are used in traditional events, including traditional wedding parties, traditional family parties, ecclesiastical events and customary state rituals. Consuming sopi can be allowed to carry out relations between brothers and sisters in traditional bonds, where when consuming sopi can cause two impacts, namely negative and positive on the body, mental and social life of humans. The alcohol contained in the sopi drink is ethanol (CH3, CH2, OH) from the fermented juice that has been distilled. Based on Riskesdas data in 2017, sopi consumers are more in rural areas. Research that uses qualitative research aims to understand the object under study in depth, besides that it also aims to develop the concept of sensitivity to the problem at hand, explain the reality related to theoretical exploration and develop an understanding of one or more of the phenomena encountered. This research was conducted in Yawuru Hamlet, Southern Islands District, Southwest Maluku Regency. The objects in this study were 10 people including: 1 Head of Yawuru Hamlet, 2 Parents, 5 Teenagers and 2 Sopi Sellers. The data analysis technique used in this research is data reduction, data presentation and verification and data conclusion.